E-Government Practices and Organizational Performance in Malaysia Local Governments - Husin, Rohana; Othman, Abdul Aziz; Othman, Zakirah; Baharom, Norashikin (UUM Press, 2024)
e-Government implemented to enhance the quality and performance of services in the public sector. Malaysia faces various issues and challenges in developing e-Government, including organizational performance weaknesses. Therefore, empirical studies are important to demonstrate the impact of eGovernment on the performance of the public sector holistically and comprehensively, which is greatly needed to serve as input in efforts to improve the quality of e-Government. This study explores the literature on e-Government and organizational performance to see the extent of e-Government's contribution to the performance of the local government sector. To fill the research gap, an empirical study using quantitative research methods was conducted on local government in Malaysia. A total of 149 questionnaires were distributed to Local Authorities in Malaysia, and 87 questionnaires were returned. Then, the data were analysed using descriptive methodology and an inferential statistical approach. The study findings indicate that the implementation of e-Government does not have a significant impact on organizational performance. The difference results may be attributes to variations in the e- Government development index between developed and developing countries. Additional factors such as the difference acceptance level and challenges in implementation may further affect the outcomes. Therefore, the study's findings conclude that the direct relationship is not significant. It is possible that other intermediate factors or variables exist within the relationship, which could allow for the study to be tested indirectly.